Genomics and Hearing Impairment - Keats, Bronya J. B.; Berlin, Charles I.

(untitled) (Genome Research, 1999)
Hearing impairment is clinically and genetically heterogeneous. There are >400 disorders in which hearing impairment is a characteristic of the syndrome, and family studies demonstrate that there are at least 30 autosomal loci for nonsyndromic hearing impairment. The genes that have been identified encode diaphanous (HDIA1), α-tectorin (TECTA), the transcription factorPOU4F3, connexin 26 (GJB2), and two unconventional myosins (MYO7A and MYO15), and four novel proteins (PDS,COCH, DFNA5, DFNB9). The same clinical phenotype in hearing-impaired individuals, even those within the same family, can result from mutations in different genes. Conversely, mutations in the same gene can result in a variety of clinical phenotypes with different modes of inheritance. For example, mutations in the gene encoding MYO7A cause Usher syndrome type IB, autosomal-recessive nonsyndromic hearing impairment (DFNB2), and autosomal-dominant nonsyndromic hearing impairment (DFNA11). Additionally, the mouse ortholog of theMYO7A gene is the shaker-1 gene. Mouse models such asshaker-1 have facilitated the identification of genes that cause hearing impairment in humans. The availability of high-resolution maps of the human and mouse genomes and new technologies for gene identification are advancing molecular understanding of hearing impairment and the complex mechanisms of the auditory system.